One Single Amino Acid for Estimation the Content of Total Free Amino Acids in Qingkailing Injection Using High-Performance Liquid Chromatography-Diode Array Detection - Li Zhang; Xue Wang; Jiankun Su; Haiyu Liu; Zhixin Zhang; Lingling Qin; Cheng He; Long Peng; Mingxing Guo; Xiaoyan Gao (Journal of Analytical Methods in Chemistry)
Qingkailing injection (QKLI), a modern traditional Chinese medicine preparation, has been widely used in clinics due to its fast and significant efficacy in treatment of high fever. The free amino acids (AAs) were considered to be the most abundant active ingredients indisputably. So developing an accurate and simple determination method to measure the contents of total free AAs in QKLI is very crucial. In current study, the accurate and simple method of using one single standard AA for simultaneous quantification of multiple AAs (One for M) in QKLI was developed. Particularly, the calculation methods and the robustness of relative correction factors (RCFs) were investigated systematically. No statistically significant difference between these two quantification methods of One for M and classic regression equation was found by the t-test (P  =  95%, P>0.05). The results showed that the precision (RSD < 4.88%), the robustness (RSD < 4.04%), and the average recoveries (94.11%–107.94%) of this newly proposed method all met the requirements for content determination. This One for M method will provide a scientific reference for the quantitative determination of AAs in other traditional Chinese medicines and their preparations owing to its accuracy and simplicity.